Maternal nutrition counselling is associated with reduced stunting prevalence and improved feeding practices in early childhood: a post-program comparison study - Mistry, Sabuj Kanti (Nutr J, 2019)
BACKGROUND: Despite progress, suboptimal feeding practices and undernutrition particularly in the form of stunting still remains a major issue among children aged less than 5 years in Bangladesh. Since mothers are the primary caregivers of young children, maternal nutrition counselling can be effective in improving knowledge and practices on child feeding. The Building Resources Across Communities (BRAC) initiated a nutrition counselling intervention using its essential health care (EHC) skeleton in 114 sub-districts of Bangladesh in 2012. This study assessed the role of this intervention on the prevalence of stunting and feeding practices among children aged less than 5 years. METHODS: The data was collected as part of a nationwide cross-sectional survey, which followed a two-stage cluster random sampling procedure and was conducted between October 2015 and January 2016. The present study analyzed the information of 3009 mother-children dyads from two selected survey areas: i) areas where the EHC package was delivered (comparison; n = 1452), ii) areas with EHC plus nutrition counselling package (intervention; n = 1557) was delivered. The Chi-square test was done to compare the child feeding practices and stunting prevalence between intervention and comparison. The degree of strength of the association of stunting and the intervention was estimated using a mixed-effect logistic regression model. RESULTS: The study revealed that the prevalence of stunting was significantly lower in areas where the intervention was delivered compared to the comparison areas (29% vs. 37%, P < 0.001). Furthermore, after adjusting for administrative zone, household wealth quintile, child’s age, gender, maternal age, education, occupation, cluster disparity, and variation between study groups, it was seen that the risk of stunting was 25% lower in the intervention areas compared to the comparison areas (aOR: 0.75, 95% CI: 0.60–0.94; P = 0.012). Optimal child feeding practices were also more common among mothers from intervention areas than those of the comparison areas (exclusive breastfeeding: 72.7 vs. 59.4%, P = 0.008; feeding 4+ food groups: 42.9 vs. 34.1%, P < 0.001; having minimum acceptable diet: 31.2 vs. 25.3%, P = 0.017; feeding multiple micro-nutrient powder: 16.2 vs. 7.4%, P < 0.001). CONCLUSIONS: The study highlighted that nutrition counselling of mothers may be effective in reducing childhood stunting with concomitant improvement in optimal feeding practices in children under 5 years of age. The frontline community health workers can be trained to counsel mothers on optimal child feeding practices and this could help reduce the prevalence of stunting.